Characterization and Evaluation of Vermicomposting Materials - Filipović Adrijana; Mandić Ana; Hadžiabulić Alisa; Johanis Hana; Stipanović Antonio; Brekalo Helena (Ekológia (Bratislava), 2023)
The agricultural sector and growing food production needs rely on chemical fertilizers. This initially had positive effects on production, but over the last decade, the negative impacts of overuse have resulted in low crop productivity, increased pest and disease infestation, soil degradation, and consequent adverse effects on environmental parameters. As one of the possibilities in organic farming, we found vermicomposting as the most sustainable practice. For the assembly of vermicomposting, mature cattle manure was utilized in three different combinations with organic material and earthworm inoculations (the household waste, the grass clippings, and mixture). The experiment was set up by random block design in three replications. Analyses of qualitative parameters of the final product showed a pH reaction from neutral to slightly alkaline. The nitrogen compound varied between 2.7% and 2.9% and the organic carbon varied between 45.59% and 47.41%, showing a C/N ratio of 16.7‒16.67. The potassium content varied between 1.1% and 1.2% K2O, and the phosphorus content varied from 0.3% to 0.5%. The experiment gave quite good results of vermicomposting of household waste with manure, showing a neutral pH reaction, optimal content of ash and carbon with almost similar and good NPK contents and increased C/N ratio of 16.7, and with satisfying levels of trace elements and the heavy metal content under the limits. This combination of household waste and manure also showed best characterization of humic and fulvic acids in vermicompost, ranging from 1505 to 1778 cm−1 and from 729 to 998 cm−1, respectively. These results indicate that vermicomposting can increase the quality of the final product.